SOSIALISASI DAN EDUKASI SISWA-SISWI SD NEGERI 4 BLANGJERANGO HUTAN KITA TANGGUNGJAWAB KITA: MERAWAT ALAM SEJAK DINI - Ridwan Ridwan; Triaty Handayani; Jumadil Akhir; Dahlan Dahlan; Tuti Arlita; Misdi Misdi; Iskandar Iskandar (Jurnal Abdi Insani, 2026)
This activity aimed to educate and build environmental awareness among the students of SD N 4 Blangjerango. Early introduction and education play a vital role in fostering a healthy and sustainable ecosystem. The activity was attended by approximately 40 students from grades IV–VI. The method applied began with the delivery of material and the screening of an educational video, followed by a hands-on tree planting practice within the school environment. During the implementation, the students showed great enthusiasm in participating in the whole series of activities. The preparation of engaging materials complemented by animated videos successfully attracted students’ interest in learning and enhanced their understanding of the topic, as demonstrated by their active participation in answering quizzes. Overall, this community service activity was comprehensively designed, starting with theoretical learning on the importance of preserving nature and the environment and concluding with tree planting. It is expected that this activity will broaden students’ knowledge and instill awareness from an early age to protect nature and the environment, encouraging them to play an active role both at school and at home in supporting environmental conservation.